2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7319537
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of wireless neural signals through a 0.18µm CMOS low-power amplifier

Abstract: Abstract-In the field of Brain Machine Interfaces (BMI) researchers still are not able to produce clinically viable solutions that meet the requirements of long-term operation without the use of wires or batteries. Another problem is neural compatibility with the electrode probes. One of the possible ways of approaching these problems is the use of semiconductor biocompatible materials (silicon carbide) combined with an integrated circuit designed to operate with low power consumption. This paper describes a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The 4 channel speed is up to 800 kbps, using a 10-bit, 20kHz analog to digital conversion, in accordance to the max specific absorption rate (1.6W/kg) defined by the Federal Communications Commission. Summary of the results for the Cortex chip in comparison with published results for similar circuits may be found in [11], where it is shown that our chip has the following advantages: better PSRR and power consumption performance; smaller area per channel; AC instead of DC coupling compared with off-the-shelf chips.…”
Section: Implantable Neural Interfacesmentioning
confidence: 89%
See 1 more Smart Citation
“…The 4 channel speed is up to 800 kbps, using a 10-bit, 20kHz analog to digital conversion, in accordance to the max specific absorption rate (1.6W/kg) defined by the Federal Communications Commission. Summary of the results for the Cortex chip in comparison with published results for similar circuits may be found in [11], where it is shown that our chip has the following advantages: better PSRR and power consumption performance; smaller area per channel; AC instead of DC coupling compared with off-the-shelf chips.…”
Section: Implantable Neural Interfacesmentioning
confidence: 89%
“…Fig. 4 shows one such low-power neural signal amplifier chip, named Cortex, fabricated using 0.18µm CMOS process technology integrated in an area of 0.40 mm 2 [11]. The chip has 4 channels, total power consumption of only 144µW, and is impedance matched to our SiC implantable neural interface electrodes.…”
Section: Implantable Neural Interfacesmentioning
confidence: 99%